The Role of a Notary in the Distribution of Inheritance Based on the Inheritance System of Indonesian Citizens - Al Jawad Alkaf, Mohamad Taqi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
. This study examines and analyzes the role of a notary in the distribution of inheritance based on the inheritance system of Indonesian citizens. Analyze the notary's constraints in the distribution of inheritance based on the inheritance system of Indonesian citizens, and formulate the ideal role of the notary in the distribution of inheritance based on the inheritance system of Indonesian citizens which guarantees legal certainty for heirs. The research method used in this study is sociological juridical, while the data collection method used is library research by collecting legal materials in the field and interviews. The data analysis method was carried out qualitatively and then presented descriptively. This research resulted in the notary's accountability authority in making a testamentary deed which still follows the provisions in article 16 UUJN Law No. 2 of 2014 concerning the Office of a Notary. Article 16 of this UUJN makes provisions regarding the requirements for a notary in forming a deed, if one of the conditions referred to is not met, the deed in question only has the power of proof as a private deed. Notaries who violate these provisions may be subject to sanctions in the form of written warnings, dishonorable discharges. In addition to being subject to these sanctions, the party that suffers a loss can demand reimbursement of costs, compensation, and if it is proven that the notary has committed a violation of the UUJN, such as falsifying the identities of the parties, falsifying signatures, then the notary can be held criminally responsible. The results of the study found that the role of a notary in the distribution of inheritance based on the inheritance system of Indonesian citizens, in serving the public in accordance with professional ethical morals and laws is to confirm acts in private law in the form of authentic deeds as perfect evidence with the aim of providing legal certainty as well as protection. law to related parties. Notaries have authority in the distribution of Islamic inheritance, but according to Notary Muhammad Sauki, SH, it is the court that has full authority to determine recognition and termination legally. Keywords: Inheritance; Law; Notary.